2006
DOI: 10.1042/bj20060598
|View full text |Cite
|
Sign up to set email alerts
|

Mouse testicular hyaluronidase-like proteins SPAM1 and HYAL5 but not HYALP1 degrade hyaluronan

Abstract: Besides SPAM1 (sperm adhesion molecule 1; formerly named PH-20), further hyaluronidase-like proteins, HYAL5 (hyaluronoglucosaminidase 5) and HYALP1 (hyaluronoglucosaminidase pseudogene 1) are also expressed in murine testicular tissue. As they share a high degree of sequence similarity with known hyaluronidases, all three polypeptides could potentially exhibit hyaluronidase activity, a function that is beneficial for spermatozoa in order to penetrate the hyaluronan-rich cumulus, which surrounds the oocyte. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…It should be noted that a research group has reported that Hyalp1, in addition to Ph-20 and Hyal5, is enzymatically functional in sperm penetration of the cumulus in the mouse (Zhang et al, 2005;Miller et al, 2007), although other workers (Reitinger et al, 2007) provide evidence that recombinant Hyalp1 is incapable of hydrolyzing hyaluronan.…”
Section: Sperm Penetration Through the Cumulus Massmentioning
confidence: 99%
“…It should be noted that a research group has reported that Hyalp1, in addition to Ph-20 and Hyal5, is enzymatically functional in sperm penetration of the cumulus in the mouse (Zhang et al, 2005;Miller et al, 2007), although other workers (Reitinger et al, 2007) provide evidence that recombinant Hyalp1 is incapable of hydrolyzing hyaluronan.…”
Section: Sperm Penetration Through the Cumulus Massmentioning
confidence: 99%
“…HYAL3 and HYAL4 lack hyaluronidase activity and seem to play a non-significant role in constitutive HA degradation (Harada & Takahashi 2007, Kaneiwa et al 2012. Similarly, HYALP1 that is present in mouse testis does not degrade HA (Reitinger et al 2007). The role of SPAM1 is discribed later in fertilisation paragraph.…”
Section: Ha Turnover and Signallingmentioning
confidence: 99%
“…Recently, it was reported that platelet-derived HYAL2 cleaves HA into fragments that are specific for inflammatory and angiogenic signaling [5]. Additionally, HYALP1 is recognized as a pseudogene in the human, but the degrading activity for HA was found in the mouse [21]. Presence of all HAase except for HYALP1 in the horse has been predicted from corresponding genomic sequences, but there is no report concerning the analysis of these activities.…”
mentioning
confidence: 99%
“…Among these, HYAL1 and HYAL2 usually found in serum are considered as major somatic HAase [4], while SPAM1 is well known as testicular HAase [21]. HYAL1 has acidic pH optima, and its upregulation is found in several metastatic carcinomas, suggesting a potential prognostic marker and therapeutic target [10,11,23].…”
mentioning
confidence: 99%
See 1 more Smart Citation